Efficiency of Built-up Land Use on the Socio-Economic Conditions of Cities: Case Study of Bandar Lampung City - Hutama, Surya Tri Esthi Wira; Persada, Citra; Mustofa, Asep Nurul ajiid; Wijaya, Indra Hadi; Gumano, Hendri Natanael (Jurnal Planologi, 2024)
Dynamic city development has an impact on land consumption levels, as an effort to increase city capacity, so this is not a sustainable option both socially and economically. As one of the provincial capitals on the island of Sumatra and the city closest to the island of Java, the city of Bandar Lampung certainly experiences the same demands regarding the use of built-up land. In identifying these conditions, this article uses a decoupling analysis method of built-up land area, population and local revenue. This research uses NDBI (Normalized Difference Built-Up Index) to describe built-up land, population and LGR (Local Government Revenue) to describe the social and economic conditions of Bandar Lampung City. The results of the NDBI analysis from 2014 to 2022 show that built-up land in Bandar Lampung City has reached 61.67%. In the same period, the city's population increased by an average of 6.01% and Bandar Lampung City's LGR increased by an average of 13.55% in 2022 amounting to IDR 645 billion. In the decoupling analysis of built-up land to population, Bandar Lampung City has an expansive negative decoupling category, so there are indications that the growth of built-up land is not adjusting to the number of residents to be accommodated. In the decoupling analysis of built-up land against PAD, the decoupling index falls into the Expansive coupling category, which means that built-up land and PAD have increased, but the growth of built-up land is higher than the PAD of Bandar Lampung City. In both conditions, it shows that population growth and local income of Bandar Lampung City is still below the growth of built-up land, so it is indicated that the growth of built-up land in Bandar Lampung City is less efficient.